'Keys to Paradise': Libraries, Literature, and Literacy in Palestine. Issue 4 (2nd October 2021) - Moore, Lindsey
Abstract: Despite the devastating effects of the 1948 'Nakba' (catastrophe) on Palestinian cultural life, Palestinian writers insist on the significance of libraries and wider book culture and contribute to ongoing efforts to retrieve a continually besieged Palestinian heritage. Beginning with an emblematic library scene in Isabella Hammad's The Parisian (2019) before tracking ways in which modernity and colonialism have been negotiated in the Khalidi Library in Jerusalem; Ibrahim Nasrallah's novel Time of White Horses (2007/2016); and memoirs by Jabra Ibrahim Jabra ( The First Well, 1987/2012), Fadwa Tuqan ( A Mountainous Journey, 1985/1990), and Ghada Karmi ( In Search of Fatima: A Palestinian Story, 2002), this article argues that creative literature sheds light on who has (and had) access to libraries in Palestine/Israel and the worldly axes on which Palestinian book culture has been conceived.